An in situ atomic force microscope for normal‐incidence nanofocus X‐ray experiments. (10th August 2016) - Vitorino, M. V.; Fuchs, Y.; Dane, T.; Rodrigues, M. S.; Rosenthal, M.; Panzarella, A.; Bernard, P.; Hignette, O.; Dupuy, L.; Burghammer, M.; Costa, L.
Abstract : A novel in situ high‐speed X‐ray atomic force microscope was used in situ in normal‐incidence X‐ray experiments to characterize radiation damage on semiconducting organic thin films. Local morphological damage occurring at specific timescales was observed and compared with the corresponding variation of the diffraction patterns. Abstract : A compact high‐speed X‐ray atomic force microscope has been developed for in situ use in normal‐incidence X‐ray experiments on synchrotron beamlines, allowing for simultaneous characterization of samples in direct space with nanometric lateral resolution while employing nanofocused X‐ray beams. In the present work the instrument is used to observe radiation damage effects produced by an intense X‐ray nanobeam on a semiconducting organic thin film. The formation of micrometric holes induced by the beam occurring on a timescale of seconds is characterized.